The Sports in Training the Learners with Special Needs - Baltabayev, E.; Saidakov, E.; Telakhynov, E.; Mendigaliyeva, Sh.A.; Kulzhabayev, A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Sport has relatively recently ceased to be an applied institution of social life. If earlier the sport had a strictly defined additional orientation (for example, it served the purposes of increasing the combat training of the army), then after the Second World War, sport becomes a means of demonstrating the prestige of the state, reaching the international level. Sport becomes a professional activity and an independent direction of the commercial life of the society. This paper is a preliminary research which gathers quantitative and qualitative information about social bonding for two categories of stake-holders: intellectually disabled athletes and partners from mainstream schools, training and competing in unique teams. This approach aimed at: identifying the perception of self-concept and self-esteem among ID athletes in relation to their social integration, determining the way ID athletes think they are perceived by their school friends and partners within Special Olympics events, identifying the positive effects on both personal and social levels, by participating in Sports events, identifying the partners’ perception related to the athletes’ abilities and possibility to advocate in this respect. All data confirmed that regular training and Sports competition attendance leads to greater social inclusion, an interesting self-concept and self-esteem perception of the athletes, as well as certain inside ways of viewing the positive outcomes of delivering such educational programs.